Implementation of Integrated E-Learning and Microteaching in Engineering: A Case Study of University of Botswana - A Agarwal; Pitso I; Dintwa E (JETL (Journal of Education, Teaching and Learning), 2020)
It is indispensable for the instructors imparting competencies should have the capability to perform their task efficiently and effectively for the development of workforce skills. In this paper, we discussed the application of combining Micro-lecture methodology with the latest e-learning techniques in a core-engineering course. Audio-visual facilities enabled smart classrooms with micro-lectures using point-based videos, PPTs and images save more time for students to engage more towards practical in the laboratory and to understand the concept easily, which instigates students’ interest and creativeness. This study aims to investigate the effect of using the microteaching methodology in integration with the latest e-learning techniques at the University of Botswana. To achieve this objective evolution is done by considering different pass percentages and online software-based student evolution of course and teaching system. The post-application results showed that the group showed a good rating in grades, presence and knowledge. Students rating received were good i.e. 4.2 and 4.3 in teaching and major course evolution on a scale of five with the pass percentage of 73.1% showing 23% increments from the previous year’s results and excellent reviews.